Determinação da atividade protetora dos inibidores de corrosão. II-Métodos eletroquímicos - Giannetti, Biagio Fernando; Centellas, Francesc; Cabot, Pere Lluis; Garrido, Jose Antonio; Pérez, Ernesto; Sumodjo, Paulo Teng-An; Benedetti, Assis Vicente; Iha, Koshun (Eclética Química, 1995)
.